ANALYSIS OF SOCIAL SKILLS AND MEANING OF LIFE: A STUDY OF MADRASAH ALIYAH STUDENTS - Hardjo, Suryani; Dewi, Salamiah Sari; Wahyuni, Nini Sri; Siregar, Nurmaida Irawani; Triastuti, Neni (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
The aim of this research is to understand how adolescents' social skills relate to their understanding of the meaning of life. This research uses a qualitative descriptive type of research which aims to analyze the social skills and meaning of life of Madrasah Aliyah X students in Medan City. The research method used was descriptive qualitative by collecting data through interviews with 5 students at Madrasah Aliyah X in Medan City. The research results show that there is a relationship between social skills and understanding the meaning of life in adolescents. The results can provide insight to educators and parents about the importance of developing social skills in helping teenagers live their teenage years better. In addition, this research also provides further understanding of how adolescents respond to social challenges and how this can influence their understanding of life goals. Therefore, the recommendation from this research is the need for a holistic approach in adolescent education which includes the development of social skills and understanding the meaning of life. Apart from that, there needs to be support and guidance from parents and educators in helping teenagers live their teenage years better.